STATEGI PENGELOLAAN ZAKAT PRODUKTIF BADAN AMIL ZAKAT KABUPATEN KARANGANYAR DALAM RANGKA PENGENTASAN KEMISKINAN - Andi Triyawan; Khairunnisa Sana Shafiyyah (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The poverty in Indonesia is the long-term problem which it has not been solved by the government. The number of poor people that recorded by Central Bureau of Statistics in Karanganyar is 108.461 inhabitants (2014). Islam has a high attention to take the poverty and the backwardness down from the poor man, because the poverty in Islam is the big danger for the people and not a few people who fall civilization only because of poverty. For solving this problem, Islam has the exact alternative. Islamic Economic system has two instruments which can solve the long-term poverty problem in Indonesia they are zakat and cash waqf. Zakat is the one of economics’ element and the pillars of Islam which must be implemented by every Moslem. Zakat is already widely distributed to several mustahik such as an indigent, poor, orphan, street children and other. And we can see also that zakat has been distributed to fund the development of infrastructure such us mosque, employment and other. But, most of distributed zakat is the consumptive zakat. Whereas the effective zakat for economic growth is the productive zakat which educates mustahik to attempt and to manage zakat fund until he can be muzakki later. From the background, the writer’s research is about the productive zakat management strategy in order towards poverty reduction. And the purpose of it is to know about the productive zakat management strategy in BAZNAS Karanganyar and its role for poverty reduction. The method of this research is descriptive qualitative method that reveals the problem or the reality as what happened until it can reveal the fact and the real image of the object. And to get the data, the writer use interview technique and written records about the productive zakat in BAZNAS Karanganyar. For the data analysis, the writer use the technique of data reduction, data display and inference aboutthe review on the research results. The research’s result is the productive zakat management strategy in BAZNAS Karanganyar has two categories, collection strategy and distribution strategy. The collection strategy applicated with payroll deduction of the moslem government employees in SKPD Karanganyar amount 2,5%, shuttle service zakat and formation the unit of zakat collection in several villages and mosques. And the distribution strategy applicated in “Karanganyar Makmur” program which includes the course of computer and automotive; the training of bag tailor industry; the goat livestock development in several villages in Karanganyar; financing sellers and small businessmen; the cow livestock development; and the other about the sharia business unit and Baitul Maal in several subdistricts. And from the application programs in BAZNAS Karanganyar, these programs are intended to improve the standard of living mustahik from economic, ability and moral side so that poverty can be overcome by any cause. From the result of research, for increasing the potential of the productive zakat, BAZNAS Karanganyar ought to be careful and to objectify the programs about the productive zakat. And for mustahik ought to keep attention and to increase zakat funds’ productivity until the poverty reduction with the productive zakat can be embodied.Keywords: Productive Zakat, BAZ, Poverty Alleviation, Management StrategyREFFERENCESAl-Ghazali (1994) Rahasia Puasa dan Zakat-Terjemahan oleh Muhammad  Al-Baqir-(Bandung: Karisma)Al-Qur’anul KarimAmalia, Kasyful Mahali (2012), Jurnal-Potensi dan Peranan Zakat dalam Mengentaskan Kemiskinan di Kota Medan (Medan)Departemen Agama (1993), Pedoman Zakat, (Jakarta: Proyek Pembinaan Zakat dan Wakaf)Departemen Agama (1996) Pedoman Zakat 9 Seri (Jakarta: Departemen Agama)DikutipolehK.H.DidinHafidhhuddin(2002)dalambuku,ZakatDalamPerekonomian Modern. (Jakarta: Gema Insani)Muhammad dan Ridwan Mas’ud (2005). Zakat dan Kemiskinan Instrumen Pemberdayaan Ekonomi Umat. (Yogyakarta: UII Press)Profil BAZNAS Kabupaten KaranganyarQadir, Abduracchman (2001)Zakat Dalam Dimensi Mahdah dan Sosial.Cet.2 (Jakarta: PT. Raja Grafindo Persada)Ridwan  Mas’ud dan Muhammad (2005) Zakat  dan  Kemiskinan  Instrumen Pemberdayaan Ekonomi Umat (Yogyakarta: UII Press)Suara Merdeka, 26 April 2016, 10.36 WIBTim BAZNAS Kabupaten Karanganyar, Laporan Kegiatan Tahun 2015Transkip Wawancara, 002/WWCR/AGUNGSYARIAH/IV/2016Transkrip Wawancara, 001/WWCR/BAZNAS/IV/2016Wahbah Az-Zuhayly (1995) Zakat  Kajian  Berbagai  Mazhab (Bandung:  PT Remaja Rosda Karya)www.baznaskaranganyar.com www.karanganyarkab.bps.go.id